STRUKTUR DAN NILAI PENDIDIKAN DALAM ANTOLOGI CRIKAK AKU, DASAMUKA LAN SENGKUNI KARYA PARPAL POERWANTO SERTA RELEVANSINYA SEBAGAI MATERI AJAR MENELAAH TEKSCRITA CEKAK DI SMA - Catur Ernawati Suprihatin; Suyitno Suyitno; Djoko Sulaksono (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2019)
The purpose of this research is to describe: (1) the structure of a short story collection Aku Dasamuka lan Sengkuni; (2) the students Value are contained in collection of short stories Aku Dasamuka lan Sengkuni; (4) the relevance of of short story Aku Dasamuka lan Sengkuni as text material inhigh school class X. This is a descriptive qualitative study with psychological literature approach. The data using of a short story collection Aku Dasamuka lan Sengkuni Parpal Poerwanto’s work. Sampling technique is  using purposive sampling. The data collection technique use of document analysis and interview. Validity of data were taken through theory of triangulation. Data analysis techniques using interactive model analysis which includes four component: (1) collecting data (2) data reduction,(3) data display, (4) concluting drawing.  The summary of this study are: (1) structure of theshort story collection Aku Dasamuka lan Sengkuni included themes, characters, setting, plot, point of view and speeches. Between elements are interrelated from a complete story; (2) the educational values contained in the short stories collection Aku Dasamuka lan Sengkuni are the religious, moral, social, culture. Of the four values is dominated by moral value; and (4) The relevance of the short stories collection Aku Dasamuka lan Sengkuni written by Prapal Poearwanto is suitable to use as material in Senior High School. Because content and language easily understood,contains the value of a positive learners,as well as structural elements of a clear and united to form the unity of the story.